Treatment History Characteristics Associated With Use of Isocarboxazid: A Nationwide Register-Based Study. Issue 2 (March 2022) - Holm, Magnus; Larsen, Jens Knud; Ishtiak-Ahmed, Kazi; Speed, Maria; Gasse, Christiane; Østergaard, Søren Dinesen
Abstract: Purpose/Background: The monoamine oxidase inhibitor isocarboxazid (Marplan) is occasionally used in the treatment of depression, but there is only little knowledge on the nature of the use of isocarboxazid in clinical practice. We aimed to identify treatment history characteristics associated with this use. Methods/Procedures: Via the nationwide Danish registers, we identified all adult incident users of isocarboxazid in the period from 2001 to 2018, as well as up to 5 matched controls using another antidepressant (matched on date of redeemed prescription, age, sex, and region of residence). The 5-year treatment history of the isocarboxazid users and the controls was assessed via the Danish registers. The association between treatment history characteristics and isocarboxazid use was examined by multivariate conditional logistic regression. Findings/Results: We identified 1455 isocarboxazid users and 7045 controls using another antidepressant. The following characteristics were associated with statistically significant increased likelihood of receiving isocarboxazid treatment: Prior treatment with a selective serotonin reuptake inhibitor (odds ratio [OR], 1.80 with 95% confidence interval [CI], 1.46–2.23), a serotonin-norepinephrine reuptake inhibitor (OR, 4.90; 95% CI, 4.08–5.89), a noradrenergic and specific serotonergic antidepressant (OR, 1.56; 95% CI, 1.30–1.88), a tricyclic antidepressant (OR, 5.05; 95% CI, 4.19–6.08), other antidepressants (OR, 4.74; 95% CI, 3.74–6.01), lithium (OR, 6.70; 95% CI, 5.08–8.83), an antipsychotic (OR, 1.43; 95% CI, 1.19–1.73), and each diagnosis of depression received in relation to psychiatric hospital treatment (OR, 1.31; 95% CI, 1.23–1.39). Forty percent of those initiating isocarboxazid had received treatment with drugs from 5 or more different psychopharmacological classes in the 5 preceding years. Implications/Conclusions: These findings suggest that isocarboxazid is typically used for treatment-resistant depression, consistent with guideline recommendations.